Neudamm (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2020)
86 JPEG files of visit to Neudamm research farm and training farm near Windhoek
Keywords: Fieldwork; Education; Agricultural laborers; Karakul sheep; Agriculture; Germany; Karakul Farming; Karakul Sheep Industry